IMMOBILIZATION AND APPLICATION OF PARTIAL PURIFIED LOVASTATIN PRODUCED FROM LOCAL ISOLATE ASPERGILLUS TERREUS A50 USING SOLID STATE FERMENTATION - Al-Sa’ady, A. J. R.; Aziz, G. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This work was designed to study the free and immobilized partial purified lovastatin in various applications. The results of HMG-CoA reductase inhibition showed enzyme inhibition at 10 mM of standard and partial purified lovastatin with specific activity 0.056 and 0.062 U/mg protein respectively, compared with specific activity 0.277 U/mg protein without inhibitor. The results of the thermal stability and storage time on lovastatin for inhibition of HMG-CoA reductase demonstrated that the standard and partial purified lovastatin were stabled in temperatures between 20-40 ᵒC, then the stability begun to decrease at 45 ᵒC, while lovastatin was stable in storage time between 1- 8 hours, then the stability begun to decrease after ten hours at 40 ºC. The results of MIC for lovastatin were demonstrated that most tested concentration were showed antibacterial activity of free and immobilized partial purified lovastatin against Candida albicans, Escherichia coli, and Staphylococcus aureus with MIC values ranging from 15 to 75 µg/ml. Whereas the results of minimum bactericidal concentration (MBC) and minimum fungicidal concentration (MFC) showed that C. albicans, E. coli, and S. aureus had no growth with concentration ranging from 55 to 75, 55 to 75, and 30 to 75 µg/ml, respectively. As well as the results of the cytotoxic impact using MTT experiment indicated that partial purified lovastatin caused a reduction in cells viability (p ≤ 0.05) at a dose-dependent manner on MCF-7 cell lines, with a calculating IC50 of 138.1 µg/ml, compare with normal cell line (WRL 68 Cell Line) at IC50 of 198.7 µg/ml.